Islamic Considerations In Recognizing And Pricing Intellectual Assets - Sadeghzadeh, Akbar; Taghi Alavi, Seyyed Mohammad (The International Journal of Accounting and Business Society, 2005)
Intellectual property right (IPR), intellectual capital (IC), intellectual assets (IA) and the similar terminology are becoming more fashionable and gaining more importance and attraction as knowledge-based economy (KBE) takes over the traditional economy gradually. Although the ï¬eld ages about one centuryâ€˜, it still is not well-organized, hence is a very demanding discourse. The discipline is still immature and "there is still a great deal of room for experimentation" (IF AC 1998,18). Recognition and pricing of IA and IC are two important areas among the various subâ€”ï¬elds of the areas of IPR and KBE. Reporting in the intellectual capital and developing intellectual capital measures and reporting practices remain one of the key challenges for the accounting profession (IF AC 1998,18). As the latest and more complete divine religion and the formal guidance of God to His creatures Islam prescribes solutions to all human problems including to the serious problems we face inrecognizing and pricing IA and IC. The dynamic nature of Islamic jurisprudence is responsive to the problems which appear in congruence with social and technological changes. This research delves in the Islamic literature pertaining to "recognizing, and pricing intellectual assets". The aim is to investigate how Islam, based on the Islamic logic, legitimizes "intellectual rights" and how Islamic considerations are taken into account in recognizing and valuing IA and IC. The bases of Islamic reasoning in this case are: the Verse: "fulï¬ll your promiseâ€œ, the famous citation from the Holy Prophet Mohammad (P.B.U.H.):"people are predominant over their propertiesâ€3, â€œcommon lawâ€â€œ and the "tradition of the wise"4, as the ï¬fth proofÃ©. The results, it is hoped, will enhance the completion of the discipline and eventually will boost development, particularly in Muslim countries. Key terms: Intellectual assets, Knowledge-based economy, Islam, Entrepreneurship and SMEs, Development.